Indication for Unicompartmental Knee Replacement versus Osteotomy around the Knee - Lobenhoffer, Philipp (The Journal of Knee Surgery, 2017)
Unicompartmental medial or lateral osteoarthritis of the knee is found in up to 50% of all osteoarthritic patients and may be addressed surgically either by knee osteotomies or unicompartmental replacements. The limits for indicating one procedure or the other are somehow not defined. This article discusses the diagnostic algorithm and the most important decision factors. A long-leg radiograph and formal deformity analysis is mandatory. If constitutional or posttraumatic metaphyseal deformity in the frontal plane is detected and the opposite compartment is intact, an osteotomy should be considered. The result is not depending on age and grade of osteoarthritis. Unicompartmental knee arthroplasty is indicated in substantial osteoarthritis of one compartment (bone-on-bone) with intact ligaments and a functionally intact contralateral compartment. The anatomy of the femur and tibia should be normal with no gross osseous deformity. Age, obesity, or asymptomatic patellofemoral degeneration are not considered exclusion criteria for those surgical procedures.
Keywords: knee osteoarthritis; constitutional deformity; joint preservation; osteotomy; unicompartmental knee arthroplasty